2002
DOI: 10.1093/nar/30.11.2565
|View full text |Cite
|
Sign up to set email alerts
|

Acridine-modified, clamp-forming antisense oligonucleotides synergize with cisplatin to inhibit c-Myc expression and B16-F0 tumor progression

Abstract: The c-myc protooncogene plays a key role in the abnormal growth regulation of melanoma cells. We have targeted three polypurine sequences within the mouse myc mRNA with acridine-modified, clamp-forming antisense oligonucleotides (AS ODNs) in an effort to inhibit growth of murine melanoma cells. These ODNs are unique in that they hybridize to the target mRNA by both Watson-Crick and Hoogsteen hydrogen bond interactions, forming a triple-stranded structure. At a concentration of 3 microM E1C, E2C and E3C inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…As previously observed in other uses of intercalating agents (Brunet et al, 2005;Stewart et al, 2001Stewart et al, , 2002, we have found that psoralen activity was less important than the acridine one (Figs. 1B and 2).…”
Section: Names Sequencessupporting
confidence: 86%
See 1 more Smart Citation
“…As previously observed in other uses of intercalating agents (Brunet et al, 2005;Stewart et al, 2001Stewart et al, , 2002, we have found that psoralen activity was less important than the acridine one (Figs. 1B and 2).…”
Section: Names Sequencessupporting
confidence: 86%
“…Acridine and psoralen both comprise hydrophobic tricyclic ring and present similar mode of intercalation. Acridine might provide a more stable hybridization and a better intracellular delivery (Brunet et al, 2005;Stewart et al, 2002). Psoralen is actually mainly used in association with irradiation, as a photoactive DNA crosslinker or as a mutagen of triplex sites (Wang et al, 1995).…”
Section: Names Sequencesmentioning
confidence: 99%
“…When administered in combination with cisplatin, INX-6295 produces a complete tumor regression in approximately 30% of treated mice . The efficacy of cMyc downregulation to inhibit cell proliferation and to synergize with cisplatin in melanoma cells has been subsequently observed by other authors by using psoralen-and acridine-modified ASOs (Stewart et al, 2001(Stewart et al, , 2002. A dose-escalation phase I clinical study in combination with cisplatin has been completed on patients with solid tumors and lymphomas (Gelmon et al, 2001).…”
Section: C-mybmentioning
confidence: 87%
“…23 This chemotherapy-sensitivity characteristic of leukemia encourages researchers to find more specific and potent drugs. For instance, several agents have been found that reduce the expression of c-Myc oncoprotein, work in cell lines 24,25 and inhibit the dimerization of Myc/Max protein. [26][27][28] In the present study, we prepared recombinant c-Myc and Max encompassing the human-origin DNA binding (basic) and dimerization (HLHZip) domains, tested the inhibitory effect of 6480 small molecules on the formation of the c-Myc/Max/DNA complex, and selected 5 compounds as potent inhibitors.…”
Section: Introductionmentioning
confidence: 99%